2020
DOI: 10.1111/his.14047
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1 expression and infiltration by CD4+ and FoxP3+ T cells are increased in Xp11 translocation renal cell carcinoma and indicate poor prognosis

Abstract: Aims: Interaction between programmed death-1 ligand (PD-L1) and its receptor programmed death 1 (PD-1) on T cells inactivates antitumour immune responses. PD-L1 expression has been associated with poor prognosis in renal cell carcinoma (RCC) and predicts adverse outcome. This study was designed to evaluate the impact of PD-L1 expression and the immune microenvironment on the clinical outcome in Xp11 translocation renal cell carcinoma (TRCC) and, therefore, their potential relevance as prognostic biomarkers. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
(33 reference statements)
2
11
0
Order By: Relevance
“…Other challenges to the use of PD-L1 as a biomarker include the availability of numerous and treatment-specific antibodies, differential expression of PD-L1 between primary RCC and metastases, remodeling of PD-L1 expression by anti-angiogenic treatment, and the need to use refined Response Evaluation Criteria In Solid Tumors (RECIST) criteria to measure the atypical response to immune checkpoint inhibitors [32]. Nevertheless, PD-L1 may have potential as a prognostic biomarker in specific subtypes of RCC, such as Xp11 translocations, where high PD-L1 expression has been associated with lower recurrence-free survival [33].…”
Section: Discussionmentioning
confidence: 99%
“…Other challenges to the use of PD-L1 as a biomarker include the availability of numerous and treatment-specific antibodies, differential expression of PD-L1 between primary RCC and metastases, remodeling of PD-L1 expression by anti-angiogenic treatment, and the need to use refined Response Evaluation Criteria In Solid Tumors (RECIST) criteria to measure the atypical response to immune checkpoint inhibitors [32]. Nevertheless, PD-L1 may have potential as a prognostic biomarker in specific subtypes of RCC, such as Xp11 translocations, where high PD-L1 expression has been associated with lower recurrence-free survival [33].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have indicated that the prognostic and predictive value of T cells infiltrated in formalin-fixed and parrffin-embedded specimens in RCC (11,12). However, to the best of our knowledge, the present study is the first to identify the relationship between peripheral blood T lymphocyte subsets and the prognosis of patients with ccRCC.…”
Section: Discussionmentioning
confidence: 67%
“…PD-L1 staining in tumor cells was significantly more frequent in papillary (18%) and chromophobe (19%), than in clear cell RCC (6%). Only few studies have earlier studied multiple RCC subtypes [ 18 , 24 , 26 , 28 , 49 , 50 ] and the existing data on differences in PD-L1 expression between RCC subtypes are conflicting. Our observations are in line with studies that have also reported lower rates of PD-L1 positivity in clear cell compared to papillary (0–16% vs 27–32% [ 18 , 26 ]) or in chromophobe RCC (0% vs 35% [ 18 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies have earlier studied multiple RCC subtypes [ 18 , 24 , 26 , 28 , 49 , 50 ] and the existing data on differences in PD-L1 expression between RCC subtypes are conflicting. Our observations are in line with studies that have also reported lower rates of PD-L1 positivity in clear cell compared to papillary (0–16% vs 27–32% [ 18 , 26 ]) or in chromophobe RCC (0% vs 35% [ 18 ]). However, there are also studies showing equally high or even higher PD-L1 positivity rates in clear cell RCCs than in other renal tumor subtypes [ 26 , 28 , 49 ].…”
Section: Discussionmentioning
confidence: 99%